Seismic assessment of small modular reactors: NuScale case study for the 8.8 Mw earthquake in Chile - Markou, George; Genco, Filippo (My University, 2019)
Reducing greenhouse gas emissions and improving energy production sustainability is a paramount of Chile's 2050 energy policy. This though, is difficult to achieve without some degree of nuclear power involvement, given that the geography of the country consists of many areas that are practically off-grid, whereas cannot be developed and financially exploited due to the lack of basic commodities such as water and electricity. Recently small modular reactors (SMRs) have gained lots of attention by both researchers and world policy makers for their promised capabilities of enhanced safety systems, affordable costs and competitive scalability. SMRs can be located in remote areas and at this time are being actively developed in Argentina, USA, Brazil, Russia, China, South Korea, Japan, India and South Africa. Chile's 2010 earthquake and Fukushima's 2011 nuclear disaster have increased significantly both the population's fear and opposition to Nuclear Power Energy for the possible consequences of radiation on the lives of people. This paper aims to study the seismic resistance of a typical nuclear structure, being at time proposed in Small Modular Reactors, by using earthquake conditions typically seen in Chile. Since many designs are under study, a NuScale reactor from USA is analyzed under these extreme loading conditions. The major advantages of the NuScale reactor are in the power scalability (it can go from 1 to 12 reactor cores producing from 60 to 720 MWe), limited nuclear fuel concentration, modules allocated below grade and high strength steel containments fully immersed in water. The cooling effect beyond Design Basis Accident is ensured indefinitely, which induces a significant safety factor in the case of an accident. For the purpose of this study a detailed 3D detailed structural model was developed, reproducing the NuScale reactor's reinforced concrete framing system, where nonlinear analyses was performed to assess the overall mechanical response of the structure. The framing system has been tested under high seismic excitations typically seen in Chile (Mw > 8.0), showing high resistance and capability to cope with the developed forces due to its design. Based on a Soil-Structure Interaction analysis, it was also found that the NuScale framing system manages to maintain a low-stress level at the interaction surface between the foundation and the soil, where the structural system was found to be able to withstand significant earthquake loads. Finally, further investigation is deemed necessary in order to study the potential damages of the structure in the case of other hazards such as tsunami events, blast loads, etc.